Internal crisis communication (ICC) framework in high risk industry: A qualitative study from key informants' perspectives - Bahtiar Mohamad; Adamu Abbas Adamu; Muslim Diekola Akanmu (Cogent Business & Management, 2023)
This paper investigates the antecedents and the consequences of ICC from the perspectives of the employees and validates the framework and operational definition of ICC in high-risk industry, which is yet to be identified in the past literature. Existing academic literature are used to develop the framework and conceptualizing the variables. This is followed by direct interviews with the engineers and administrative staff of the industry to confirm the antecedents and consequences of ICC. The qualitative data is analyzed using QSR Nvivo version 12.0 software while a deductive content analysis is used to classify the data using themes and keywords. The employees presented different views on high-risk industry as related to the antecedents and consequences of ICC. The findings show that the employee crisis perceptions are clearly played as a consequence of internal crisis communication in their workplace. This study further makes clarification by developing new concepts of ICC with clearer insights on the antecedents and consequences. This new development poses as blueprint to help the high-risk industries by successfully integrating the ICC framework into corporate management strategies. Also, this study revisited the concepts of ICC in a specific context and confirmed its antecedents and consequences through development of new measurements.
Keywords: 650; employee crisis perception; high-risk industry; internal crisis communication; Malaysia; management commitment; safety culture; supportive environment